Tuberculous bursitis around the knee mimicking benign soft tissue tumor - Che Ahmad, Aminudin; Osman Cassim, Samsudin; Shukur, Mohd Hassan (Faculty of Medicine, International Islamic University Malaysia, 2004)
We report a case of a man presenting with painless diffuse swelling over his right knee region with the clinical and radiological features suggesting a benign soft tissue tumour. Surgical removal of the lesion was done. A histopathological (HPE) and polymerase chain reaction (PCR) examination for Mycobacterium tuberculosis DNA confirmed the diagnosis of tuberculous bursitis around the knee with joint involvement. He was treated with 6 months of antituberculous chemotherapy. Correct diagnosis was difficult and delayed because of the rarity of the condition. Modern imaging technology including magnetic resonance imaging, in particular, was not conclusive.